Clinical Characteristics of Asymptomatic Thromboembolism in Psychiatric Inpatients: A Retrospective Study - Geng Y; Zhang P; Pan Y; Wang H; Chen Y; Lai J; Hu S (Neuropsychiatric Disease and Treatment, 2024)
Yimeng Geng,1,* Peifen Zhang,1,* Yanmeng Pan,1,* Huaizhi Wang,2 Yi Chen,1 Jianbo Lai,1,3,4 Shaohua Hu1– 4 1Department of Psychiatry, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, People’s Republic of China; 2Department of Psychiatry, Wenzhou Medical University, Wenzhou, 325035, People’s Republic of China; 3The Key Laboratory of Mental Disorder’s Management in Zhejiang Province, Hangzhou, 310003, People’s Republic of China; 4Brain Research Institute of Zhejiang University, Hangzhou, 310003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shaohua Hu, Department of Psychiatry, The First Affiliated Hospital, Zhejiang University School of Medicine, The Key Laboratory of Mental Disorder’s Management, Brain Research Institute of Zhejiang University, Hangzhou, 310003, People’s Republic of China, Email dorhushaohua@zju.edu.cnPurpose: Venous thromboembolism (VTE) poses a significant threat to individuals’ health, yet its correlation with mental disorders remains underappreciated. Here, we conducted a retrospective analysis to explore the characteristics of psychiatric patients presenting with VTE.Methods: We retrospectively analyzed psychiatric inpatients with elevated plasma D-dimer levels at the Mental Health Center, First Affiliated Hospital, Zhejiang University School of Medicine, from January 2014 to January 2022. The inclusion criteria comprised comprehensive demographic and clinical profiles, including laboratory and imaging findings.Results: A cohort of 33 eligible patients was included, with plasma D-dimer levels ranging from 880 to 10,700 μg/L FEU. Significantly higher D-dimer levels were observed in patients diagnosed with severe mental disorders (SMD), such as schizophrenia and bipolar disorder, compared to those with mild mental disorders (MMD), including depression and anxiety disorders (p = 0.007). Furthermore, individuals receiving antipsychotic medications for less than one year exhibited elevated D-dimer levels compared to those on treatment for over one year (p = 0.005). However, normalization of D-dimer levels did not demonstrate a significant association with psychiatric diagnosis or treatment duration (p > 0.05).Conclusion: Our findings suggest that patients diagnosed with SMD or those undergoing antipsychotic treatment for less than one year may have elevated D-dimer levels, indicating a potential predisposition to VTE severity. This underscores the importance of recognizing VTE risk in individuals with severe mental disorders and warrants further investigation into the impact of antipsychotic treatment duration on thrombotic risk.Keywords: asymptomatic thromboembolism, D-dimer, psychiatric disorder, risk factors